👤

A= x(x-1) + 2x(x-3) ; B= (2x+3)(x-4) + (2x+3)(x+1) ; C= (3x-1)(5x+2) - (5x+2)(2-x)
A=(x+5)*-(2x+7)*; B= 4x*+20x+25
A= x3-12x*; B= x(1-x) + (x-1)(x+2) , C= (5x+1)(-3x+4) + x(10x+2)
Factoriser les expressions svp aidez moi


Répondre :

Factoriser les expressions suivantes
A= x(x-1) + 2x(x-3)
A= x²-x+2x²-6x
A= 3x²-5x
A= x(3x-5)
 
B= (2x+3)(x-4) + (2x+3)(x+1)
B= (2x+3)(x+4+x+1)
B= (2x+3)(2x+5)

C= (3x-1)(5x+2) - (5x+2)(2-x)
C= (5x+2)[(3x-1)-(2-x)]
C= (5x+2)(3x-1-2+x)
C= (5x+2)(4x-3)

A=(x+5)²-(2x+7)²   identité remarquable a²-b²
A= [(x+5)-(2x+7)][ (x+5+2x+7)]
A= (x+5-2x-7)(3x+12)
A= (-x-2)(3x+12)

B= 4x²+20x+25     IR 
B= (2x + 5)(2x+5)= (2x+5)²

A= x³-12x²
A= x(x²-12x)

B= x(1-x) + (x-1)(x+2)
B= x(1-x) -(1-x)(x+2)
B= (1-x)[(x-(x+2)]
B= (1-x)(x-x-2)
B= -2(-x+1)

C= (5x+1)(-3x+4) + x(10x+2)
C= (5x+1)(-3x+4)+2x(5x+1)
C= (5x+1)(-3x+4+2x)
C= (5x+1)(-x+4)